A conceptual framework for analyzing critical cactors of PDS learning experience and PDE employment experience - Ahmed, Masum Uddin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science, 2023.